A mistake in using Mathematical Induction

 

 

 

Question

     A sequence of real numbers  {an}  is defined as follows:

             a0 = a1 = 1,  a2 = 3  and  

             an+3 = 3an+2 – an+1 – 2an  where  n = 0, 1, 2, …

    

     Let  bk = ak+2 – ak+1ak  , where  k = 0, 1, 2, …

     Prove that  bn = 2bn-1  " n Î N .

 

 

 

 

        ‘Solution’

 

        Find the conceptual mistake in the following proof:

 

        Let P(n) be the proposition :              bn = 2bn-1

 

        For P(1),

                b0   = a2 – a1 – a0 = 3 – 1 – 1 = 1

                b1   = a3 – a2 – a1 = (3a2 – a12a0) – a2 – a1 = 2(a2 – a1 – a0)

                        = 2(3 – 1 – 1) = 2

        \    b1 = 2b0 .

        \ P(1)  is true.

 

        Assume P(k) is true for some kÎ N, that is,

                      bk = 2bk-1                                                                               (*)

       

        For P(k + 1), 

                        bk+1 = ak+3 – ak+2 – ak+1

                                = (3ak+2 – ak+1 – 2ak) – ak+2 – ak+1

                                = 2(ak+2 – ak+1 – ak)

                                = 2bk                      

        \ P(k + 1) is true.

       

        By the Principle of Mathematical Induction, P(n) is true  " n Î N.

 

 

 

 

      The Mistake

 

In the proof of  P(k + 1)  above, there is no where in which the inductive hypothesis, that is, (*)  is used.

 

In fact, the proof does not need to use Mathematical Induction at all.

 

Just write,

                bn   = an+2 – an+1 – an

                        = (3an+1 – an – 2an-1) – an+1 – an

                        = 2(an+1 – an – an-1)

            = 2bn-1

 

The proof is already completed.

 

 

 

 

      Exercise

 

If you insist to use mathematical induction, the proof of 

P(k + 1)  above should be changed in order that  (*)  is used.

It will be quite tedious to write the proof out, can you do this ?